2009
DOI: 10.1177/0890334408325072
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Incentives and Barriers to Exclusive Breastfeeding Among Periurban Ghanaian Women

Abstract: Focus group discussions were conducted to elicit the perceived incentives and barriers to exclusive breastfeeding in Ghana. Thirty-five breastfeeding women were recruited from the Manya and Yilo Krobo districts of the eastern region. Participants had a mean age of 27.5 years and had at least one child < 4 months old. Almost all of the participants believed that exclusive breastfeeding is the superior infant feeding method and should be practiced for the first 6 months postpartum. However, there was widespread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
161
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(197 citation statements)
references
References 19 publications
(32 reference statements)
27
161
2
1
Order By: Relevance
“…Nevertheless, the findings were similar to the findings of a study conducted by [15] which found out that mothers in growth monitoring program have good preventive behaviour. In this study, it also revealed that cultural beliefs and social pressure do not have any influence on mothers ability to practice exclusive breastfeeding and complementary in contrast to what was concluded by [16] on barriers in practicing exclusive breastfeeding among peri-urban mothers from Manya and Yilo Krobo in Eastern Region of Ghana. In [7] study through review of records found out that 75% of caregivers' attended growth monitoring regularly, however this study shows that about 93.7% of caregivers' were attending GMP session, probably this is because this study focused on perception of caregivers' and not records.…”
Section: Discussioncontrasting
confidence: 48%
“…Nevertheless, the findings were similar to the findings of a study conducted by [15] which found out that mothers in growth monitoring program have good preventive behaviour. In this study, it also revealed that cultural beliefs and social pressure do not have any influence on mothers ability to practice exclusive breastfeeding and complementary in contrast to what was concluded by [16] on barriers in practicing exclusive breastfeeding among peri-urban mothers from Manya and Yilo Krobo in Eastern Region of Ghana. In [7] study through review of records found out that 75% of caregivers' attended growth monitoring regularly, however this study shows that about 93.7% of caregivers' were attending GMP session, probably this is because this study focused on perception of caregivers' and not records.…”
Section: Discussioncontrasting
confidence: 48%
“…Support from family members (i.e. grandparents or the husband) was shown to have a positive impact on EBF, and this has been found in other studies [114,116,121,122,128,129]. Lack of family support was also identified as barrier in a study in India [130].…”
Section: Discussionmentioning
confidence: 55%
“…Additional barriers related to the mother were being a first time mother, her physical condition (such as nipple problems and breast pain) and negative attitudes to breastfeeding. Other studies in various countries and regions [Pakistan, Zimbabwe, United Arab Emirates, Ghana, Uganda, West Africa and China] have identified insufficient breast milk supply reported as a barrier to 6 months EBF by mothers [113,114,117,[120][121][122][123][124]. Breast conditions have been reported as a barrier in other studies conducted in the United Arab Emirates, Pakistan, Africa, and South America [113,117,121,125,126].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three studies examined maternal employment in relation to EBF practices, including fifteen crosssectional (17)(18)(19)26,31,32,(34)(35)(36)(37)(38)(46)(47)(48)(49) , four qualitative (30,33,45,50) , two mixed-methods (21,23) and two cohort studies (24,25) . Definitions of maternal employment varied across the studies and included employment status, type of occupation, return to work following childbirth and/or employment cited as a barrier to EBF.…”
Section: Prelacteal Feedingmentioning
confidence: 99%
“…Malawi Qualitative Otoo et al (33) 35 Ghana Qualitative X X Raghavan et al (43) 400 India Cohort Safari et al (49) 130 Tanzania Cross-sectional X Seid et al (34) 819 Ethiopia Cross-sectional X X Setegn et al (21) 603 Ethiopia Mixed methods X X Sharma and Kanani (37) 648 India Cross-sectional X Sohag and Memon (32) …”
mentioning
confidence: 99%